2015
DOI: 10.1111/ssqu.12180
|View full text |Cite
|
Sign up to set email alerts
|

Fair Housing Enforcement in the South and Non‐South*

Abstract: Objective We compare outcomes in racial discrimination fair housing complaints processed by southern state and local civil rights agencies to those handled by state and local agencies outside the South and the federal agency, HUD (Department of Housing and Urban Development). Methods Based on data obtained directly from HUD, we rely on a fixed effects logistic regression model with cluster‐correlated standard errors. Results First, southern local agencies are significantly more likely to provide outcomes favor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…For example, a comparison of fair housing complaints handled by the US federal government with complaints handled by state and local human rights commissions found that southern commissions were more likely to provide an outcome favorable to the complainant, thus providing a justification for SNHRI complaint-handling (and perhaps countering expectations concerning local reluctance to enforce anti-discrimination laws in the southern US). 83…”
Section: E Robustnessmentioning
confidence: 99%
“…For example, a comparison of fair housing complaints handled by the US federal government with complaints handled by state and local human rights commissions found that southern commissions were more likely to provide an outcome favorable to the complainant, thus providing a justification for SNHRI complaint-handling (and perhaps countering expectations concerning local reluctance to enforce anti-discrimination laws in the southern US). 83…”
Section: E Robustnessmentioning
confidence: 99%
“…HUD implements federal fair housing policy by investigating, conciliating, and closing Title VIII complaints. State and local civil rights agencies that assist in Title VIII enforcement under HUD’s Fair Housing Assistance Program (FHAP) use a similar process (Bullock, Lamb, and Wilk 2017; Bullock, Wilk, and Lamb 2015). In fact, the 1968 legislation created a cooperative federalism arrangement: state and local governments that pass housing discrimination laws substantially equivalent to Title VIII in terms of rights, procedures, remedies, and the availability of judicial review have the first opportunity to enforce Title VIII, ahead of the federal government (Lamb and Wilk 2010; HUD 2014).…”
Section: Intergovernmental Enforcementmentioning
confidence: 99%